Glacial erosion dynamics in a small mountainous watershed (Southern French Alps): a source-to-sink approach - Bonneau, Lucile (Earth and planetary science letters, 2016)
In this study we used major element composition, neodymium isotopes ratios (εNd) and concentration of REE to track and quantify the sediment routing in the Var sedimentary system from source (Southern French Alps) to sink (Ligurian Sea) over the last 50 ka. Our data reveal that changes in sediment sources over that period, associated with concomitant changes in the hyperpycnal (i.e. flood-generated turbidity currents) activity in the Var submarine canyon, were mainly driven by paleoenvironmental conditions in the upper basin and in particular by the presence of glaciers during the last glacial period. Based on this evidence, we determined when and how glacier-derived sediments were produced, then excavated and transferred to the ocean, allowing us to ultimately tune offshore sedimentary records to onshore denudation rates. In contrast to large glaciated systems, we found that sediment export from the Var River to the Mediterranean Sea directly responded to climate-induced perturbations within the basin. Finally, we estimated that sediment fluxes in the Var routing system were 2.5 times higher during the Last Glacial Maximum than today, thus confirming that glacier denudation rates exceed fluvial rates and that such a pattern also governs the interglacial-glacial sediment flux cycle in other small mountainous basins.
Gesehen am 10.04.2018